2010
DOI: 10.1194/jlr.p000695
|View full text |Cite
|
Sign up to set email alerts
|

Marked elevations in pro-inflammatory polyunsaturated fatty acid metabolites in females with irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS) is a common and potentially disabling, though nonfatal, medical disorder that can affect up to 20% of the population. It is the most common functional gastrointestinal disorder referred to gastroenterologists ( 1 ). Although it has evolved over the years in terms of nomenclature ( 2, 3 ), classifi cation ( 4-6 ), and appreciation of its frequency ( 7 ), a poor understanding of disease pathophysiology has remained a constant. According to the Rome III criteria, a symptom-based cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 48 publications
2
44
2
1
Order By: Relevance
“…This finding is consistent with data indicating an increase in blood levels of lipid inflammatory mediators such as prostaglandin E2 and leukotriene B4, which are known to be released from newly formed mast cells. 42 The potential activation of the innate gut immune system in IBS could be a sign of previous infection and/or ongoing low-grade inflammation. In this regard, increased faecal levels of the human beta-defensin HBD2, 43 an antimicrobial peptide produced by intestinal epithelial cells, and elevated blood concentrations of the A4-Fla2 and Fla-X bacteria-specific antibodies 44 38,46 Similarly, the Studies identified in PubMed literature search with the following key words:…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with data indicating an increase in blood levels of lipid inflammatory mediators such as prostaglandin E2 and leukotriene B4, which are known to be released from newly formed mast cells. 42 The potential activation of the innate gut immune system in IBS could be a sign of previous infection and/or ongoing low-grade inflammation. In this regard, increased faecal levels of the human beta-defensin HBD2, 43 an antimicrobial peptide produced by intestinal epithelial cells, and elevated blood concentrations of the A4-Fla2 and Fla-X bacteria-specific antibodies 44 38,46 Similarly, the Studies identified in PubMed literature search with the following key words:…”
Section: Resultsmentioning
confidence: 99%
“…24 The same strain increased polyunsaturated fatty acids (PUFAs) and exhibited anti-inflammatory effects when coadministered with α-linoleic compared with α-linoleic supplementation alone. 25,26 It is believed that the microbiota, as well as pro-and pre-biotics, can have a significant impact on the gutbrain axis, but further research in this area is needed to reveal the magnitude, mechanisms and clinical relevance of these effects.…”
Section: Effects Of the Intestinal Microbiome On The Brain-gut Axismentioning
confidence: 99%
“…mast cells and pro-inflammatory polyunsatured fatty acid metabolites were increased [9][10][11]. Other potential causes of IBS are diet and enteric flora abnormalities leading to low-grade inflammation/immune activation [12].…”
Section: Introductionmentioning
confidence: 99%